Математична модель і алгоритм машинного розрахунку коефіцієнта рециркуляції та витрати палива в тунельній хлібопекарській печі - Дудко, Сергій Дмитрович (My University, 2015)
Розглянута математична модель рециркуляційного контуру хлібопекарської тунельної печі. Виконана адаптація зазначеної моделі під потреби машинного розрахунку основних величин, що характеризують роботу циклотермічної системи — коефіцієнта рециркуляції та витрати палива. Описаний алгоритм, який передбачає виконання циклічних розрахунків у послідовності: канал — циклотермічна система в цілому — канал. Mathematical model of recirculated circuit for baking oven is studied. The adaptation of the model for machine calculation of basic values that characterize the work of the cyclothermic system - recycle ratio and fuel consumption was completed. The algorithm, providing for execution of cyclic calculation in a sequence: heating channel — cyclothermic system as a whole — heating channel, was proposed. Unlike existing methods of calculation eliminates the need to have value of combustion gas temperature in exhaust as a source data. The new method is free of this defect. To perform a complete thermal calculation of baking oven is enough to know in addition to the usual source data the temperature and flow rate of the out coming gases that are the result of the heating channels previous calculation. This method can enhances the possibility of computer simulation using in the design of new devices and debugging optimal baking modes in existing furnaces
Keywords: кафедра машин і апаратів харчових та фармацевтичних виробництв; коефіцієнт рециркуляції; витрата палива; тунельна піч; циклотермічна система; recycle ratio; fuel consumption; tunnel oven; cyclothermic system